Effects of blood meal source on blood consumption and reproductive success of cat fleas, Ctenocephalides felis - Brittny N. Blakely; John Agnew; Charlotte Gard; Alvaro Romero (Public Library of Science (PLoS), 2023)
Cat fleas, small blood-feeding ectoparasites that feed on humans and animals, cause discomfort through their bites, and can transmit numerous diseases to animals and humans. Traditionally, fleas have been reared for research on live animals, but this process requires animal handling permits, inflicts discomfort on animals, and requires money and time to maintain the host animals. Although artificial membrane-based feeding systems have been implemented, these methods are not sustainable in the long term because they result in lower blood consumption and egg production than those with rearing on live hosts. To maximize these parameters, we tested blood from four hosts to determine the most suitable blood, on the basis of blood consumption and egg production. We also tested the effects of adding the phagostimulant adenosine-5´-triphosphate to the blood to maximize blood consumption. In 48 hours, fleas fed dog blood consumed the most blood, averaging 9.5 μL per flea, whereas fleas fed on cow, cat, or human blood consumed 8.3 μL, 5.7 μL, or 5.2 μL, respectively. Addition of 0.01 M and 0.1 M adenosine-5´-triphosphate to dog and cow blood did not enhance blood consumption. In a 1-week feeding period, the total egg production was also greatest in fleas fed dog blood, with females producing 129.5 eggs, whereas females on cat, human, and cow blood produced 97.2, 83.0, and 70.7 eggs, respectively. The observed results in dog blood indicate an improvement over previously reported results in cat fleas fed with an artificial feeding system. Improving the sustainability of rearing cat flea colonies without feeding on live animals will enable more humane and convenient production of this pest for scientific research. Author summary Cat fleas cause discomfort through their bites, and can transmit numerous diseases to animals and humans. Traditionally, fleas have been reared for research on live animals, but this process requires animal handling permits, inflicts discomfort on animals, and is costly. Artificial feeding methods that warm blood and offer it through a membrane have been used but fleas often take small amount of blood and produce fewer eggs than those with rearing on live hosts. To maximize blood consumption and egg production, we offered fleas blood from four hosts to determine the most suitable blood for flea rearing. We also tested the effects of the addition of compounds that increase blood consumption (phagostimulants). Fleas fed dog blood consumed the most blood, followed by fleas fed on cow, cat, or human blood. Addition of phagostimulants did not enhance blood consumption. Fleas fed dog blood produced 129.5 eggs, whereas females on cat, human, and cow blood produced 97.2, 83.0, and 70.7 eggs, respectively. The observed results in dog blood indicate an improvement toward the production of cat fleas in the laboratory without feeding on live animals. This system will enable more humane and convenient production of this pest for scientific research.